College Student Attitudes Toward Advertising's Ethical, Economic, and Social Consequences - Beard, Fred K. (Journal of business ethics, 2003)
Little research has focused on college students' attitudes toward advertising's ethical, economic, and social consequences over the last two decades. Exploring and tracking the attitudes of college students toward advertising is important, however, for several reasons. College students represent an important segment of consumers for many marketers, negative attitudes toward advertising on the part of college students could lead to their support for restrictive regulation in the future, and there are potentially negative consequences concerning the effects of advertising that college students uniquely share with other youth markets. The results of this study – a differentiated replication of an earlier study of college students in the late 1970s – indicate the salience of various beliefs that help determine attitudes toward advertising and provide a useful benchmark for future studies. The implications of the study's findings for advertising practice and future regulation are discussed.